Earth’s Orbital Control on Organic Matter Enrichment in the Black Shales of the Wufeng–Longmaxi Formation in the Upper Yangtze Region, South China - Zhao, Shaoze; Li, Yong; Xu, Yingjiao; Cheng, Leli; Nie, Zhou; Zhao, Liang (Frontiers in Earth Science, 2022)
The Upper Ordovician Wufeng Formation through the Lower Silurian Longmaxi Formation in China’s Upper Yangtze Region is its most successful horizon for shale-gas exploration and development. In this study, the Wufeng–Longmaxi Formation black shales in the Upper Yangtze Region are analysed to determine their microstructural characteristics, total organic carbon (TOC) content, and well-log characteristics and to identify information on the parameters of Earth’s orbit from its gamma-ray (GR) data series. Then, air–sea modes are established over a long time scale. On this basis, the Earth’s orbital control on organic matter enrichment in the black shales are examined. The black shales of the Wufeng Formation and the lower Longmaxi Formation are rich in biogenic siliceous fossils and framboidal pyrite. Their TOC content, GR value and uranium (U) content increase gradually from the bottom of the Wufeng Formation to the Guanyinqiao member at its top, peak at the Guanyinqiao member, and then decrease gradually up to the Longmaxi Formation. Approximately six and seven long eccentricity cycles can be identified from the GR curves of the Wufeng Formation and the lower Longmaxi Formation, respectively. Compared with the long eccentricity maximum period, at long eccentricity minima, correspond to Earth’s cold period, the black shales have a relatively high level of enrichment of organic matter. This study can provide an important reference for the investigation of the mechanism by which Earth’s orbits control the climate and sedimentary environment as well as the mechanism of organic matter enrichment.